The three musketeers. Part I, D'Artagnan [videorecording (DVD)] - Delaporte, Matthieu; La Patellière, Alexandre de, 1971-; Rassam, Dimitri; Civil, François, 1989-; Cassel, Vincent, 1966-; Duris, Romain, 1974-; Marmaï, Pio; Green, Eva, 1980-; Dumas, Alexandre, 1802-1870 (Samuel Goldwyn Films, 2024)
D'Artagnan arrives in Paris trying to find his attackers after being left for dead, which leads him to a real war where the future of France is at stake. He aligns himself with Athos, Porthos and Aramis, three musketeers of the King.